The Implementation of Tactical Approach in Developing Football Games Performance and Understanding of Junior High School Students - Sucipto, S (Universitas Pendidikan Indonesia, 2020)
The main objective of this research is the implementation of tactical approaches towards developing junior high school students' understanding and skills in playing football. The method that is used in this research is to experiment with the pretest-posttest control group design. This research involves two groups, the first-named an experimental group with a tactical approach intervention and the second group with a technical (traditional) approach to the development of junior high school students understanding and playing skills. Two instruments are used in this study, the first is multiple-choice cognition instruments at the level of difficulty C1 to C3 which are used to measure students' understanding in playing football, the second is instruments to test playing football skills using Game Performance Instrument Assessment (GPAI). The research will be conducted on junior high school students in Bandung City. All data obtained will be analyzed using the one-way Manova technique which aims to see the influence between groups both on developing understanding and enjoyment together as well as each variable. Based on the results of the analysis, it can be concluded that implementation of tactical approaches gives an influence on students' understanding in playing football lessons and gives influence to the students games performance in playing football. AbstrakTujuan utama penelitian ini adalah mengimplementasikan pendekatan taktis terhadap pengembangan pemahaman dan keterampilan bermain sepak bola siswa SMP. Metode yang akan digunakan dalam penelitian ini adalah eksperimen dengan rancangan pretest posttest control group design. Melibatkan dua kelompok, yaitu satu kelompok eksperimen dengan intervensi pendekatan taktis dan satu kelompok dengan intervensi pendekatan teknis (tradisional) terhadap pengembangan pemahaman dan keterampilan bermain sepakbola siswa SMP. Terdapat dua instrument yang akan digunakan dalam penelitian ini yaitu (1) instrument kognisi jenis multiple choise pada tingkat kesukaran C1 sampai dengan C3 yang akan digunakan untuk mengukur pemahaman siswa dalam permbelajaran bermain sepak bola, (2) instrument tes keterampilan bermain sepakbola dengan menggunakan Game Permomance Assessment Instrumen (GPAI). Penelitian akan dilakukan pada siswa-siswi SMP dilingkungan kota Bandung. Semua data yang diperoleh akan analisis dengan menggunakan teknik manova satu jalur yang bertujuan untuk melihat pengaruh antar kelompok baik pada pengembangan pemahaman dan kesenangan secara bersama-sama maupun masing-masing variabel. Berdasarkan hasil analisis dapat disimpulkan bahwa implementasi pendekatan taktis memberikan pengaruh terhadap pemahaman siswa dalam pembalajaran sepak bola dan berpengaruh terhadap keterampilan bermain sepak bola siswa dalam pembelajaran sepak bola.